The effects of EU-funded guarantee instruments of the performance of small and medium enterprises: Evidence from France - Fabio Bertoni; Massimo G. Colombo; Anita Quas (European Investment Fund (EIF), 2018)
This paper provides a policy-oriented summary of the econometric study commissioned by the European Court of Auditors, in the context of its audit of EU-funded loan guarantee instruments.2 The study assesses the real performance effects of EU-guaranteed loans to SMEs disbursed in France during the years 2002 to 2016. The study estimates the average treatment effect of guaranteed loans over a 10-year period around disbursement, using a combination of difference-in-difference estimation, coarsened exact matching and propensity score analysis. On average, French SMEs benefitting from EU-guaranteed loans experienced additional 9% asset growth, 7% sales growth, and 8% employment growth compared to the control group. The economic significance of the effect is typically stronger for smaller and younger firms. Beneficiary SMEs also experienced 5% lower default rates. The study also estimates the effects of guaranteed loans on SME productivity. Consistent with earlier works, the analysis finds a short-run dip in productivity, accompanied by a medium-run recovery and a long-run positive effect, signalling the presence of adjustment costs in the production function following loan-induced investments. The study concludes by discussing potential implications for policy makers and further research.
Keywords: G2; H25; O16; 330; EIF; credit guarantees; credit constraints; real effects; small and medium-sized enterprises